Electronic Signatures in Law - Mason, Stephen (OBserving Law, 2016)
This fourth edition of the well-established practitioner text sets out what constitutes an electronic signature, the form an electronic signature can take, and discusses the issues relating to evidence - illustrated by analysis of relevant case law and legislation from a wide range of common law and civil law jurisdictions. Stephen Mason is a leading authority on electronic signatures and electronic evidence, having advised global corporations and governments on these topics. He is also the editor of Electronic Evidence and International Electronic Evidence, and he founded the international open-source journal Digital Evidence and Electronic Signature Law Review in 2004. This book is also available online at http://ials.sas.ac.uk/digital/humanities-digital-library/observing-law-ials-open-book-service-law.